Compassion Fatigue Resiliency Program to Reduce Compassion Fatigue of Midwifery Students in Muhammadiyah University Sidoarjo - Dewi, Mei Shinta; Norfirdausi, Tanalin; Sinambela, Frikson C (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
Compassion fatigue is a feeling of distress experienced by individuals due to being immersed in the trauma experienced by the patient. This situation is commonly experienced by social workers or health workers who are intensely dealing with and providing assistance to patients. The purpose of this study was to provide knowledge about compassion fatigue and its handling through resilience techniques. The compassion fatigue resiliency training program was given for two days to 14 students with an average age of 21-22. The training provides an increase in students' knowledge about compassion fatigue and resilience. There was also a higher decrease in student compassion fatigue at follow-up than at the post-test. It can be concluded; participants need time to practice resilience techniques in their daily lives first.